2017
DOI: 10.22516/25007440.174
|View full text |Cite
|
Sign up to set email alerts
|

El papel de los biosimilares en la enfermedad inflamatoria intestinal: una realidad en nuestro país

Abstract: ResumenLa enfermedad inflamatoria intestinal (EII) es un término con el que se conocen varias entidades, las 2 más importantes son: la colitis ulcerativa idiopática (CUI) y la enfermedad de Crohn (EC), cuyo origen es multifactorial y se caracterizan por un fenómeno inflamatorio, crónico, recurrente con diferentes grados de severidad del tubo digestivo; pero además con afectación potencial de otros órganos.En la última década ha habido un renovado interés en dichas entidades, debido a una incidencia creciente d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…In some cases, moreover, health systems do not cover all treatments, a fact which delays access to timely treatment. 28,51,52 On the other hand, the study carried out in Spain showed that indirect costs are very significant, representing 46.5% of total costs, and are mostly associated with productivity losses due to temporary absences from work and work disabilities. The analysis carried out estimated that more than 40% of active workers with IBD have been absent at some time in the last 3 months due to the disease and 10% of patients willing to have a full-time job, find involuntary part-time employees.…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 99%
See 4 more Smart Citations
“…In some cases, moreover, health systems do not cover all treatments, a fact which delays access to timely treatment. 28,51,52 On the other hand, the study carried out in Spain showed that indirect costs are very significant, representing 46.5% of total costs, and are mostly associated with productivity losses due to temporary absences from work and work disabilities. The analysis carried out estimated that more than 40% of active workers with IBD have been absent at some time in the last 3 months due to the disease and 10% of patients willing to have a full-time job, find involuntary part-time employees.…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 99%
“…48 Although in recent years there have been important advances in the diagnostic methods used, achieving a diagnosis at early stage of IBD continues to be one of the main challenges for the timely management of the disease. 15,47,52 Recent studies in Europe have revealed that in approximately 45% of cases, IBD patients take more than a year to receive a definitive diagnosis. 22 According to a similar study carried out in Brazil, where 3476 patients participated, only 30.25% of people were diagnosed within 6 months after presenting symptoms.…”
Section: Diagnosis and Management Of The Diseasementioning
confidence: 99%
See 3 more Smart Citations